Nutritional Status and Physical Fitness Level of Students in Public Elementary School 38 Lubuk Sao - Ardi, Ronal; Neldi, Hendri; Saputra, Roni (Yayasan Sekora, 2017)
His research is based on the reality in the field, especially the Lubuk Sao 38 Elementary School, the low level of physical fitness of the students. Many factors cause this, one of which is thought to be the nutritional status of students. The purpose of this study was to determine the relationship between students' nutritional status and physical fitness, especially N38 Lubuk Sao Elementary School, Tanjung Raya District, Agam Regency. This type of research is correlational. The population of this study were 72 elementary school students in Lubuk Sao, Agam Regency. Sampling using purposive sampling technique with a sample of 39 people consisting of 24 male students and 15 female students. Data collection tools are in the form of measurement of nutritional status based on BMI and physical fitness tests covering 40 meters running, hanging bent elbows, lying down, jumping upright and running 600 meters. Data were analyzed using the product moment correlation formula. The results showed (1) the correlation of nutritional status and physical fitness of male students was (rxy) 0.219 <rtab (0.404), (2) the correlation of nutritional status and physical fitness of female students was (rxy) 0.220 <rtab (0.514). From the research results, it was found that there was no correlation between nutritional status and the level of physical fitness, both male and female students at 38 Lubuk Sao Elementary School, Tanjung Raya District, Agam Regency.